2009
DOI: 10.1007/s10765-009-0653-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the True Temperature of Molybdenum and Luminous Flames from Generalized Wien’s Displacement and Stefan–Boltzmann’s Laws: Thermodynamics of Thermal Radiation

Abstract: The true temperature of thermal radiation of molybdenum and luminous flames is defined from the temperature dependences of generalized Wien's displacement and Stefan-Boltzmann's laws. For determining the true temperature of molybdenum, experimental values of either the position of the maximum of the spectral emitted density or the total emitted density are needed. It is shown that the thermal radiation of molybdenum belongs to the same universality class as that of tantalum, tungsten, and zirconium and titaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In [17,18], it was shown that in the case of a blackbody, Eq. 1 differs negligibly from the Wien displacement law [21].…”
Section: Generalized Wien's Displacement Lawmentioning
confidence: 99%
See 4 more Smart Citations
“…In [17,18], it was shown that in the case of a blackbody, Eq. 1 differs negligibly from the Wien displacement law [21].…”
Section: Generalized Wien's Displacement Lawmentioning
confidence: 99%
“…7, at the melting temperatures [23], we obtain the following values for the position of the maximum of the spectral energy density: In conclusion, it is important to note that a similar law of the relationship (Eq. 7) between the true temperature T and the position of the maximum ν max of the normal spectral energy density was obtained for tantalum, tungsten, and molybdenum [16][17][18]. This means that the emitted radiations of molybdenum, tantalum, tungsten, and stoichiometric zirconium, titanium, and hafnium carbides belong to the same universality class.…”
Section: Determination Of the True Temperature Of Stoichiometric Hafnmentioning
confidence: 99%
See 3 more Smart Citations